PANJALIN TRADITIONAL HOUSE SITE AS A MEANS OF LOCAL HISTORY EDUCATION FOR THE YOUNG GENERATION - Imas Siti Masitoh; Aksilas Dasfordate; Rufer Firma Harianja; Rahmanul (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
This study aims to analyze the Panjalin traditional house site and its potential as a means of local history education for the younger generation. The purpose of this research is to examine how the Panjalin traditional house site is a means of historical education for the community, especially in the Majalengka area. This research approach uses qualitative-descriptive methods and the researcher comprehensively collects and processes information using literature study, observations, and interviews. The results of this study show that the Panjalin traditional house site helps provide an overview of the history of Majalengka in the 15th century when the development of Islamic kingdoms in Indonesia and Dutch colonialism in the Cirebon sultanate area. The Panjalin traditional house site can be an alternative to learning local history for the younger generation, both at the school level or in general level in the Majalengka and surrounding areas. The Panjalin traditional house site has the potential to be an effective, more interesting, relaxed, and relevant historical education tool for the understanding of the history of the younger generation in Majalengka regarding the history of their community which is closer to their daily lives.